Peran Ibu dalam Berkomunikasi dan Pengelolaan Keuangan Rumah Tangga - Lucyanda, Jurica; Jamilah Mihardja , Eli; Budi Priyanto, Adi (Indonesian Journal for Social Responsibility, 2020)
This community service activity aims to provide an explanation and understanding related to the role of housewives as family managers in communicating and managing financial within the family. The special purpose of this activity is that mothers in Desa Kejapanan, Gempol, Pasuruan, Jawa Timur, can implement family communication effectively and skillfully in managing finances and making simple financial reports. The community service partners are housewives (women's groups) in Desa Kejapanan, Kecamatan Gempol, Kabupaten Pasuruan, Jawa Timur. The method used in this activity is the presentation of material and discussion/question and answer. Participants of housewives who participated in this activity were 20 people. The implementation of this activity provides understanding and motivates housewives to have good communication to build the closeness of family members and conduct simple financial records to controlling family finances. This is shown from the enthusiasm of housewives in discussions and questions related to household financial management. This community service is expected to be a follow-up activity to become a fostered village by the University of Bakrie to start a small business in order to increase household income in accordance with the condition in their area.